(untitled) (IPS Journal of Nutrition and Food Science, 2022)
Yoghurt is a cultured, semisolid and curdled food product. It is made from fermented milk by a bacterium. Whereas, the fruit yoghurts are milk products that are fermented by special cultures of Lacto bacteria. The aim of the study was to examine the nutritional quality by proximate analysis and also to find out microbiological status by total bacterial and plate count of fruit yoghurt. The variation in nutritive value and microbiological load among fresh and stored fruit yoghurt was also evaluated. The results revealed that the carbohydrates are increased in commercial yoghurt and decreased after storage in both types of yoghurts. Similarly, moisture, Ash, fat, protein and acidity were significantly increased after storage in both types of yoghurts. The pH values were significantly decreased during storage. Fruit curd was highly acidified rather than fruit yoghurts. The total viable count was also highly significant in both types of yoghurt during storage. High bacterial activity was found in fruit curd than in fruit yoghurt. Lactobacilli were identified in all fruit curd than in fruit yoghurt thermophilic bacteria were also detected.